Competências necessárias ao profissional de biblioteconomia para atuar como gestor da informação e do conhecimento - Santos, Vinicius Rodrigues Pereira dos (2023)
Given the characteristics of the master's degree in library science, librarians can play an important role as an information manager in contemporary organizations, thus contributing to the creation and dissemination of knowledge. The aim of this dissertation was to identify, classify and evaluate the competencies of the librarian as an information and knowledge manager for the creation and dissemination of knowledge in organizations. In this qualitative and exploratory research, it was conducted a systematic literature review, documentary research, and field research with a committee of experts. The theoretical framework on librarian competencies was established based on the C.H.A.V.E, T-SHAPED, and Hard Skills/Soft Skills competency models. Documentary research protocol enabled identification of 55 technical and personal competencies required in job advertisements for librarians in the country. These competencies were segregated into primary, secondary, and additional, as indicated by 132 experts who responded the field research. The 15 competencies identified as priorities for the librarian to act as an information and knowledge manager were (in alphabetical order): adaptability, commitment, communication, creativity and innovation, emotional intelligence, ethics, interpersonal relationships, knowledge management techniques, learning, management, organization, proactivity, problem-solving, science and technology and teamwork. In addition, the 55 identified competencies were also classified according to the three competency models (C.H.A.V.E, T-SHAPED, and Hard Skills/Soft Skills). In conclusion, the competencies´ list indicates the possibility of the librarian's role as an information and knowledge manager in organizations, highlighting the importance of technical and personal skills for the efficient performance of this function.